A CTCF-independent role for cohesin in tissue-specific transcription - Schmidt, Dominic; Schwalie, Petra C.; Ross-Innes, Caryn S.; Hurtado, Antoni; Brown, Gordon D.; Carroll, Jason S.; Flicek, Paul; Odom, Duncan T.

(untitled) (Genome Research, 2010)
The cohesin protein complex holds sister chromatids in dividing cells together and is essential for chromosome segregation. Recently, cohesin has been implicated in mediating transcriptional insulation, via its interactions with CTCF. Here, we show in different cell types that cohesin functionally behaves as a tissue-specific transcriptional regulator, independent of CTCF binding. By performing matched genome-wide binding assays (ChIP-seq) in human breast cancer cells (MCF-7), we discovered thousands of genomic sites that share cohesin and estrogen receptor alpha (ER) yet lack CTCF binding. By use of human hepatocellular carcinoma cells (HepG2), we found that liver-specific transcription factors colocalize with cohesin independently of CTCF at liver-specific targets that are distinct from those found in breast cancer cells. Furthermore, estrogen-regulated genes are preferentially bound by both ER and cohesin, and functionally, the silencing of cohesin caused aberrant re-entry of breast cancer cells into cell cycle after hormone treatment. We combined chromosomal interaction data in MCF-7 cells with our cohesin binding data to show that cohesin is highly enriched at ER-bound regions that capture inter-chromosomal loop anchors. Together, our data show that cohesin cobinds across the genome with transcription factors independently of CTCF, plays a functional role in estrogen-regulated transcription, and may help to mediate tissue-specific transcriptional responses via long-range chromosomal interactions.